DAMPAK PENGGUNAAN BAHASA DAERAH DALAM PEMBELAJARAN TERHADAP MOTIVASI BELAJAR SISWA DI SD GMIT FATUNISUAN KECAMATAN MIOMAFFO BARAT - Tualaka, Yunanci Noni; Heryon Mbuik; Cornelia Naitili (STKIP Subang, 2026)
This study aims to explore the impact of local language use, particularly the Dawan (Uab Meto) language, on students’ learning motivation at SD GMIT Fatunisuan, Miomaffo Barat District. The research is grounded in the linguistic realities of rural settings where students are more familiar with their mother tongue than with Bahasa Indonesia, the national language used as the formal medium of instruction. Such a situation often leads to difficulties in comprehension, low classroom participation, and decreased motivation to learn. This study employed a qualitative descriptive approach with data collected through observation, in-depth interviews, and documentation. The participants consisted of two teachers and several fourth-grade students. The findings reveal that integrating local language into classroom instruction enhances students’ psychological comfort, strengthens teacher-student interaction, and promotes active participation during learning activities. Students demonstrated greater enthusiasm, confidence, and willingness to learn when the lessons were delivered using a language familiar to their everyday lives. The results confirm that the use of local language in learning has a positive and significant influence on students’ motivation. These findings suggest that educational policies in multilingual contexts should allow contextual use of mother tongues as an instructional strategy that not only supports academic understanding but also contributes to the preservation of local cultural identity.